Algorithms for Purchasing AIDS Vaccines - Bishai, David; Lin, Maria K.; Kiyonga, C.W.B. (World Bank, Washington, DC, 2014)
The authors delineate two different algorithms for the purchase of AIDS vaccines, to show how differences in policy objectives can greatly affect projections of the number of courses of vaccine that will be needed. They consider a hypothetical vaccine costing ten dollars to produce, and offering sixty percent, seventy five percent, and ninety percent reductions in the risk of HIV for ten years. For each of the world's ten major geographic divisions, they sue published estimates of the risk of AIDS, the value of medical costs averted, and the value of potential productivity losses. Under the "health sector" algorithm - in which purchases are made to minimize the impact of AIDS/HIV on government health spending - 766 million courses of vaccine would be purchased. Under the "societal" algorithm - in which purchases are made to minimize the impact of AIDS/HIV on health spending and GDP - more than 3.7 billion courses of vaccine would be purchased. Under an "equity" model - allocating vaccines to everyone in the world at high risk, as if they had the financial resources of Western Europeans - vaccine would be offered to 4.7 billion people. For a Western European man, reducing the risk of AIDS/HIV would be a $789 concern; in Africa, the comparable risk would be a $48,577 crisis. The authors conclude that financing AIDS vaccines solely on the fixed budget of a ministry of health, means large vulnerable populations wouldn't receive the vaccine. Allocating the vaccine based on society's ability to pay would still exclude many poor infants who would probably be immunized if they were born in more developed regions. Policymakers concerned about equity in health care must redouble efforts to making the financing of development, and distribution of AIDS vaccines, a global, not a regional concern.